RELEVANSI PENGATURAN DALAM PENYELESAIAN PERMASALAHAN SENGKETA DI INDONESIA BERDASARKAN KETENTUAN UNDANG-UNDANG NOMOR 5 TAHUN 1986 JUNCTO UNDANG-UNDANG NOMOR 9 TAHUN 2004 TENTANG PERADILAN TATA USAHA NEGARA (PTUN) - Ismawati Septiningsih; Ainuun Ridayanti; Itok Dwi Kurniawan; Suyatno Suyatno (RESEARCH FAIR UNISRI, 2023)
The Unitary State of the Republic of Indonesia is a dynamic rule of law aimed at creating a prosperous, secure and orderly nation and state. PTUN's mission is to resolve disputes between states and citizens. Disputes often arise as a result of policies and actions. The ideal of human sovereignty has not yet been fully realized as rulers continue to exceed their power. Rulers can abolish social control, leading to a concentration of power. A common legal research method is to analyze the laws and regulations relevant to the issue. The results show that the diversity and dynamics of complex social issues lead to ethical standards of administration that are enhanced by the quality of inclusion and underpinned by the differentiation of values, attitudes and norms of conduct. In the policies and actions of government officials who can build public confidence. Efforts to adhere to government ethical standards can be maintained through strategies that increase clarity of purpose.